Altered Glucose Metabolism and Glucose Transporters in Systemic Organs After Bariatric Surgery - Oh, Ju Hun; Kang, Chan Woo; Wang, Eun Kyung; Nam, Jung Ho; Lee, Soohyun; Park, Kyeong Hye; Lee, Eun Jig; Cho, Arthur; Ku, Cheol Ryong (Frontiers in Endocrinology, 2022)
The Roux-en-Y gastric bypass (RYGB) is highly effective in the remission of obesity and associated diabetes. The mechanisms underlying obesity and type 2 diabetes mellitus remission after RYGB remain unclear. This study aimed to evaluate the changes in continuous dynamic FDG uptake patterns after RYGB and examine the correlation between glucose metabolism and its transporters in variable endocrine organs using 18F-fluoro-2-deoxyglucose positron emission tomography images. Increased glucose metabolism in specific organs, such as the small intestine and various fat tissues, is closely associated with improved glycemic control after RYGB. In Otsuka Long-Evans Tokushima Fatty rats fed with high-fat diets, RYGB operation increases intestine glucose transporter expression and various fat tissues’ glucose transporters, which are not affected by insulin. The fasting glucose decrement was significantly associated with RYGB, sustained weight loss, post-RYGB oral glucose tolerance test (OGTT) area under the curve (AUC), glucose transporter, or glycolytic enzymes in the small bowel and various fat tissues. High intestinal glucose metabolism and white adipose tissue-dependent glucose metabolism correlated with metabolic benefit after RYGB. These findings suggest that the newly developed glucose biodistribution accompanied by increased glucose transporters is a mechanism associated with the systemic effect of RYGB.